2022
DOI: 10.3389/fcell.2022.988866
|View full text |Cite
|
Sign up to set email alerts
|

Nramp: Deprive and conquer?

Abstract: Solute carriers 11 (Slc11) evolved from bacterial permease (MntH) to eukaryotic antibacterial defense (Nramp) while continuously mediating proton (H+)-dependent manganese (Mn2+) import. Also, Nramp horizontal gene transfer (HGT) toward bacteria led to mntH polyphyly. Prior demonstration that evolutionary rate-shifts distinguishing Slc11 from outgroup carriers dictate catalytic specificity suggested that resolving Slc11 family tree may provide a function-aware phylogenetic framework. Hence, MntH C (MC) subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 110 publications
1
32
0
Order By: Relevance
“…Prior work suggested that reevaluating the phylogenetic structure of MCb clade may delineate a putative precursor lineage (MCb ie ) from LB’s MCbs (MCb gut ): NCBI sequence wp_092092601.1 from the Carnobacteriaceae Pisciglobus halotolerans (Uniprot ID: A0A1I3CNB9), representing a cluster of sequences (seqs>70% aa id), demonstrated both MCb most basal branching node and relatively little specific divergence compared to the rest of MCb clade [7]. Detailing the phylogenetic relationships of A0A1I3CNB9 clade, i.e., MCb ie , amid eukaryotic prototype Nramps and other bacterial MntH C clades (Figure 1B) confirmed both its basal position relative to the rest of MCb homologs, i.e., MCb gut , and the relative sequence conservation of its members.…”
Section: In Silico Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior work suggested that reevaluating the phylogenetic structure of MCb clade may delineate a putative precursor lineage (MCb ie ) from LB’s MCbs (MCb gut ): NCBI sequence wp_092092601.1 from the Carnobacteriaceae Pisciglobus halotolerans (Uniprot ID: A0A1I3CNB9), representing a cluster of sequences (seqs>70% aa id), demonstrated both MCb most basal branching node and relatively little specific divergence compared to the rest of MCb clade [7]. Detailing the phylogenetic relationships of A0A1I3CNB9 clade, i.e., MCb ie , amid eukaryotic prototype Nramps and other bacterial MntH C clades (Figure 1B) confirmed both its basal position relative to the rest of MCb homologs, i.e., MCb gut , and the relative sequence conservation of its members.…”
Section: In Silico Resultsmentioning
confidence: 99%
“…The 3D modeling properties of MCb gut templates differ from other MntH C clades, apparently due to intrinsic carrier plasticity and the presence of flexible loops [6, 7]. Based on the candidate MCb synapomorphy (Figure 3BC) one could expect that AF2/CF models of native MCb ie carriers would resemble known MCb gut structures either modeled or solved.…”
Section: In Silico Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All DMT1 subtype classifications (pN-I, pN-II, aN-I, aN-II) were previously assigned 39 . Prokaryotic MntH (MA) transporters were used as the outgroup.…”
Section: Supporting Figuresmentioning
confidence: 99%